2009
DOI: 10.1176/appi.ajp.2008.08030383
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Lipid and Glucose Monitoring in Commercially Insured Patients Treated With Second-Generation Antipsychotic Agents

Abstract: Despite statistically significant improvements after the ADA guidelines were issued, monitoring for plasma lipids and glucose in this population remains low. Clinicians and administrators responsible for the health of at-risk populations should implement new approaches for effective monitoring of major modifiable risk factors for medical morbidity and mortality in patients taking second-generation antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
2
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 33 publications
11
134
2
6
Order By: Relevance
“…This frequency of 11% of baseline glucose testing for children and adolescents ages 2 through 18 prescribed SGAs is similar to that reported by Haupt et al 15 This work also has limitations. The large national insurance plans participating as Mini-Sentinel data partners only have access to laboratory results data from a subset (not all) of their enrollees.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This frequency of 11% of baseline glucose testing for children and adolescents ages 2 through 18 prescribed SGAs is similar to that reported by Haupt et al 15 This work also has limitations. The large national insurance plans participating as Mini-Sentinel data partners only have access to laboratory results data from a subset (not all) of their enrollees.…”
Section: Discussionsupporting
confidence: 86%
“…An epidemiologic study by Haupt et al 15 employing laboratory claims data from patients of all ages up to 65 years treated with SGAs between 2000 and 2006 demonstrated that metabolic monitoring was not conducted as recommended. They documented cardiometabolic monitoring practices had not changed substantially since the FDA warnings, SGA product label revisions, and national monitoring guidelines issuance.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…50,51 Specifically, ADA/APA guidelines recommend quarterly weight and BMI measurements; annual monitoring of blood pressure, fasting glucose, and waist circumference; and fasting lipids every 5 years or Bmore frequently if clinically indicated.^5 1 Unfortunately, over 10 years after publication of these diabetes screening guidelines, 70 % of people taking SGAs remain unscreened for diabetes or dyslipidemia. [52][53][54][55][56] Based on estimates that 20 % of the 19 million US adults with SMI have diabetes 26 and 70 % of them are not screened for diabetes 53,57 ; over 2 million Americans have unidentified diabetes. Given that undiagnosed diabetes costs over $4,000 per person, 58 this failure to identify diabetes among people with SMI represents a missed opportunity to prevent morbidity and translates into over $8 billion in annual preventable costs to the healthcare system.…”
Section: Screening For Type 2 Diabetes and Other Cardiovascular Diseamentioning
confidence: 99%
“…73 Just as in other countries, 93 the availability of physical health screening guidelines has not ensured minimal screening standards are met for physical health problems such as CVD. Screening and monitoring protocols and guidelines are available in Australia 45,46,54,70,75,77,94 (see Table 2) and overseas.…”
Section: Discussionmentioning
confidence: 99%